Fabrication of paper devices via laser-heating-wax-printing for high-tech enzyme-linked immunosorbent assays with low-tech pen-type pH meter readout. Issue 3 (20th January 2017) - Le, Shangwang; Zhou, Hui; Nie, Jinfang; Cao, Chaohong; Yang, Jiani; Pan, Hongcheng; Li, Jianping; Zhang, Yun
Abstract : This work reports a laser-heating-wax-printing method to fabricate paper devices for developing paper-based ELISAs that use pen-type pH meters for quantitative readout. Abstract : In this work, a new method named laser-heating-wax-printing (LHWP) is described to fabricate paper devices for developing sensitive, affordable, user-friendly paper-based enzyme-linked immunosorbent assays (P-ELISAs) that initially use common pen-type pH meters for portable, quantitative readout. The LHWP enables a rapid patterning of wax in paper via one step of heating the wax layer coated on the paper surface using a mini-type CO2 laser machine. Wax-patterned paper microzones created in this way are utilized to conduct the pen-type pH meter-based P-ELISAs with enzyme-loaded SiO2 microbeads for highly efficient signal amplification of each antibody–antigen binding event. The results show that this new P-ELISA system is quantitatively sensitive to the concentrations of a model protein analyte in buffer samples ranging from 12.5 to 200 pg mL −1, with a limit of detection of ca . 7.5 pg mL −1 (3 σ ). Moreover, the satisfactory recovery results of assaying several human serum samples validate its feasibility for practical applications.